Conducting General Social Surveys as Self-Administered Mixed-Mode Surveys. Issue 2 (24th September 2021) - Wolf, Christof; Christmann, Pablo; Gummer, Tobias; Schnaudt, Christian; Verhoeven, Sascha
Abstract: This article discusses the current challenges of conducting a General Social Survey (GSS) in face-to-face mode and evaluates the alternative of fielding these surveys in self-administered mixed-mode (web, mail) instead. Based on data from Germany, it first illustrates the stark decline of participation in face-to-face surveys since 2002 and reports a strong increase in the cost of conducting these surveys over the same period. It then discusses the possibility of implementing GSS-type surveys in a self-administered design and reports results from a mode experiment implemented in the German part of the European Values Study (EVS) 2017/18. The results of the experiment indicate that self-administered mixed-mode surveys are a viable alternative for cross-sectional general population surveys in Germany; they shorten the fieldwork period and lead to higher response rates, while being more cost-efficient than face-to-face surveys. Despite the finding that the sample composition deviates from the general population in both modes, the face-to-face mode represents the population slightly better.